2016
DOI: 10.5505/tjtes.2016.37571
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Tadalafil and Eriythropoietin in Experimental Spina Cord Injury

Abstract: BACKGROUND: This experimental study was an investigation of the efficacy of erythropoietin and tadalafil in rats with induced spinal cord injury (SCI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The meta-analysis indicated that SCI rats receiving EPO therapy showed a significant locomotor function recovery in all studies (1 d to 28 d, P < 0.01; Figure 2 ). After the intervention of EPO, the BBBs score increased [1 d, 21 studies ( 18 , 25 , 35 37 , 41 , 43 – 46 , 48 , 49 , 51 , 54 , 59 , 61 , 63 65 ), WMD = 0.69, 95% CI [0.22, 1.15], P = 0.004; 3 d, 17 studies ( 18 , 25 , 35 , 42 , 43 , 46 , 48 , 49 , 58 , 63 , 66 70 ), WMD = 2.50, 95% CI [1.69, 3.31], P < 0.00001; 7 d, 24 studies ( 18 , 25 , 35 , 36 , 42 , 43 , 45 , 46 , 48 , 49 , 54 , 58 , 59 , 63 , 65 , 67 69 , 71 – 74 ), WMD = 3.31, 95% CI [2.21, 4.41], P < 0.00001; 14 d, 20 studies ( 18 , 25 , 35 , 42 , 43 , 45 , 46 , 48 , 49 , 58 , 59 , 63 , 65 , 67 69 , 73 , 74 ), WMD = 3.80, ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis indicated that SCI rats receiving EPO therapy showed a significant locomotor function recovery in all studies (1 d to 28 d, P < 0.01; Figure 2 ). After the intervention of EPO, the BBBs score increased [1 d, 21 studies ( 18 , 25 , 35 37 , 41 , 43 – 46 , 48 , 49 , 51 , 54 , 59 , 61 , 63 65 ), WMD = 0.69, 95% CI [0.22, 1.15], P = 0.004; 3 d, 17 studies ( 18 , 25 , 35 , 42 , 43 , 46 , 48 , 49 , 58 , 63 , 66 70 ), WMD = 2.50, 95% CI [1.69, 3.31], P < 0.00001; 7 d, 24 studies ( 18 , 25 , 35 , 36 , 42 , 43 , 45 , 46 , 48 , 49 , 54 , 58 , 59 , 63 , 65 , 67 69 , 71 – 74 ), WMD = 3.31, 95% CI [2.21, 4.41], P < 0.00001; 14 d, 20 studies ( 18 , 25 , 35 , 42 , 43 , 45 , 46 , 48 , 49 , 58 , 59 , 63 , 65 , 67 69 , 73 , 74 ), WMD = 3.80, ...…”
Section: Resultsmentioning
confidence: 99%
“…MDA has been widely used as a convenient biomarker for lipid peroxidation of omega-3 and omega-6 fatty acids due to its easy reaction with thiobarbituric acid ( 66 , 67 ). Three studies measured MDA levels after SCI and found that MDA levels were significantly lower in the EPO group than the matched group of controls [2 studies ( 42 , 58 ), WMD = −0.63, 95% CI (−1.09 to −0.18), P = 0.007; Figure 5 ] to detect its antioxidative effect.…”
Section: Resultsmentioning
confidence: 99%